Pengaruh Campuran Media Tanam Terhadap Pertumbuhan dan Produksi Kubis Bunga (Brassica oleracea L.) - Khairul Ansar; Hilda Susanti; Lyswiana Aphrodyanti (Agroekotek View, 2019)
The research, entitled influence of the media mix towards growth and production of cauliflower (Brasicca olerace L.) have been implemented in March until may 2017 on the field of Lambung Mangkurat, Agriculture Faculty. The experimental design used a random complete design (RAL) with 5 treatment M0 = (control) 8 kilogram soil + NPK, M1 = (7.5 kilogram soil + 0.5 kilogram manure + NPK) M2 = (7 kilogram soil + 0.5 kilogram sand + 0.5 kilogram manure + NPK), M3 = (7 kilogram soil + 0.5 kilogram chaff + 0.5 kilogram manure + NPK), M4 = (7 kilogram soil + 0.5 kilogram chaff ash + 0.5 kilogram manure + NPK). The treatment has 4 replication and 20 units experiment. Observations include the increase of leaves number, early flower emergence, cabbage flower diameter, cabbage flower wet weight. Results show media mixture has influence on plant growth and the production of cauliflower. Soil mixture, chicken manure, NPK get the chaff or ash gives growth and production of cauliflower the best compared to other mixture media.